Perencanaan Pengembangan Jaringan Pipa PDAM Tirta Bahari Kota Tegal dengan Simulasi Epanet 2.2 - Marlina, Linda; Diantoro, Wahudin; Fatkhurozak, Fatkhurozak (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Clean water is a vital resource that must be sustainably available to support human life. In Tegal City, the provision and distribution of clean water is primarily managed by Perumdam Tirta Bahari through a piping distribution system. However, several challenges persist, including high leakage rates, unserved customers, and areas not yet covered by the distribution network. One such underserved area is the Citraland neighborhood. This study aims to design a clean water distribution network using the EPANET 2.2 software, which simulates the hydraulic conditions of piping systems. The results of the network design are expected to meet water demand efficiently and effectively, while also expanding the service coverage of Perumdam Tirta Bahari. Through a technical and modeling approach, the Citraland area is projected to become a new service zone with optimal pressure and discharge levels according to standards.